Formation of cheddar cheese analogues using canola oil and ultrasonication – A comparison between single and double emulsion systems. (June 2020) - Leong, Thomas S.H.; Ong, Lydia; Gamlath, Charitha J.; Gras, Sally L.; Ashokkumar, Muthupandian; Martin, Gregory J.O.
Abstract: Cheddar cheese analogues were produced from skim milk in which canola oil was emulsified using ultrasound to form either single (O/W) or double emulsions (W1/O/W2). The double emulsion cheese analogues (DECH) had a distinct microstructure and retained small skim milk droplets, dispersed in the fat phase, for more than 7 months of ageing at 4 °C. The single emulsion cheese analogues (SECH), prepared with the same fat content as control cheeses, produced comparable yields of cheese and whey, with similar composition, although the fat droplets were more spherical and showed greater coalescence. The DECH cheese with skim milk encapsulated in the oil droplets was harder, melted less and showed more free fatty acid development over 7 months of aging than the control cheeses. The SECH cheeses were softer than the control and also melted less effectively but did not show greater free fatty acid development.